FARMLAND REAL ESTATE INVESTMENT TRUSTS - Leković Milјan; Cvijanović, Drago; Jakšić, Milena (Economics of Agriculture, 2018)
The modern era has brought the need for the establishment of farmland real estate investment trusts. The establishment of these trusts positively affects growth and development of agricultural sector and ultimately contributes to global poverty reduction and sustainable development of the world economy and society. The research objective is to highlight the importance of these institutional investors as a new mechanism for investing in farmland and an additional source of fnancing for the agricultural sector. No studies on this issue in domestic and insufficient number of them in foreign literature have been a motive for the conducted research. The intention is to introduce investment community with the basic characteristics of farmland real estate investment trusts, as well as the key factors that arouse interest and lead to investment in farmland as new asset class.